Assessing Pain Intensity in Children with Chronic Pain: Convergent and Discriminant Validity of The 0 To 10 Numerical Rating Scale in Clinical Practice - Danielle Ruskin; Chitra Lalloo; Khushnuma Amaria; Jennifer N Stinson; Erika Kewley; Fiona Campbell; Stephen C Brown; Michael Jeavons; Patricia A McGrath (Pain Research and Management)
BACKGROUND: In clinical practice, children are often asked to rate their pain intensity on a simple 0 to 10 numerical rating scale (NRS). Although the NRS is a well-established measure for adults, no study has yet evaluated its validity for children with chronic pain.